Implementation of Scrum Framework Agile Method to Develop Integrated Asset Management Information System at Universitas Diponegoro Inventory Module - Fauzan Abiyyu Dzaky; Defri Kurniawan (Department of Informatics, Universitas Diponegoro, 2023)
Diponegoro University Property (BMU) requires an inventory process by the assets and logistics division at least once every five years. The inventory process is still manually. So it is necessary to develop an Integrated Asset Management Information System Inventory Module. The development of an information system that used the Big Bang and Use Case Points method, in this study the Agile method with Scrum Framework will be implemented based on considerations. Scrum as a framework that implements Sprints to break down complexity and accommodate priority features that need to be built from an information system, also divides the roles in implementing development into Product Owner, Developer Team and Scrum Master. The results of implementing this method can be a solution to several problems that arise during development, that is : dividing roles with existing teams, accepting all updates and changes originating from user evaluations through mutual agreement, work transparency which can be a reference in assigning the workload of each team members, regular periodic inspections to remind each member of development targets and goals, as well as adapt to implementing conditions, especially in adjusting communication and implementation times. So make information system development time can implemented shorter.